Pengaruh Penerapan Good Corporate Governance dan Ukuran Perusahaan Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur Sektor Makanan dan Minuman Yang Terdapat di BEI Periode 2018-2021 - Lathifatul Himmah; R Hery Koeshardjono; Dyah Ayu Perwitasari (Universitas Panca Marga, 2024)
This study aims to examine the effect of the implementation of good corporate governance and company size on company value in food and beverage sector manufacturing companies contained in the IDX for the 2018-2021 period. In this study GCG can be measured by proxy managerial ownership, audit committee and independent commissioner, while company size is measured using Ln total assets. The dependent variable in this study is the value of the company measured using Tobin's Q analysis. The research method used is a quantitative method with multiple regression analysis. The sampling technique used purposive sampling and the number of samples used was 76 companies. The data used is in the form of secondary data derived from audited annual financial statements. The results of the study showed that managerial ownership, audit committee and independent commissioner partially had no effect on the value of the company. While the size of the company partially affects the value of the company.